Pengaruh Guided Imagery Relaxation Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi - Lannasari, Lannasari; Syipa Mariatuk Kibtiah; Emi Yuliza (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: One of the non-pharmacological intervention techniques that can be used is the guided imagery relaxation technique. When doing Guided Imagery Relaxation it produces endorphins. Endohrpin is a neurohormone associated with pleasant sensations so it is expected to lower blood pressure. This study aims to determine the effect of Guided Imagery Relaxation on reducing blood pressure in hypertensive patients. Method: This type of research is Quasy Experiment with a one group pretest posttest design. The sampling technique used purposive sampling with the population that will be taken in this study is the community of the Cikalongkulon Cianjur Health Center in people with hypertension aged 45-70 years who do not experience complications and do not regularly take hypertension medication. The number of samples is 16 respondents. Statistical analysis using the Wilcoxon Signed Rank T-Test. Results: From the results of the Wilcoxon Signed Rank T-Test analysis, it shows that there is a significant effect between Guided Imagery Relaxation and a decrease in blood pressure in the Working Area of ​​the Cikalongkulon Health Center, Cianjur p-value 0.002 (<0.05). Conclusion: From this study it shows that there is an effect of guided imagery relaxation on reducing blood pressure in the Working Area of ​​the Cikalongkulon Health Center.